Identifying Vulnerabilities in Systemically-Important Financial Institutions in a Macro-Financial Linkages Framework - Sun, Tao (IMF Working Papers; Working Paper ;, 2011)
This paper attempts to identify the indicators that can demonstrate the vulnerabilities in systemically important financial institutions. The paper finds that (i) indicators on leverage, liquidity, and business scope can help identify the differences between the intervened and non-intervened financial institutions during the subprime crisis; (ii) the expected default frequencies react positively to shocks to leverage, inflation, global financial stress, and global excess liquidity, and negatively to return on assets and equity prices; and (iii) leverage has been the most robust factor with a long-run causal effect on the expected default frequencies.